Welcome to KCM Project based Research in Business and Economics - Mishra, A. K. (New Perspective: Journal of Business and Economics, 2023)
This editorial highlights the need for adopting research-based teaching throughout Nepal's higher institutions, drawing insights from unique practice of project-based research teaching exercise at Kathmandu College of Management (KCM). It is perspective from the desk of editor based on experiences, observations and reviews of published and unpublished literatures. KCM undergraduate’s scholars academic research exercise from business and economics Volume 6, issue 1 for the year 2023 to overcome national researchable issue of the domain keeping priority on what is published more than that of by whom or where is published is offered to you which consists of 10 research articles after peer review and this editorial perspective. It is assured that you will have a new perspective from each and every research published here. Editorial provides imperative for Nepal's higher institutions to prioritize research-based teaching to ensure the holistic development of its students and the overall progress of the nation by managing diversity and different uniqueness among different institutions based on their objectives rather than just being follower, it is time to be leader through exercise of different education philosophy connecting society and learner in collaboration to global research based institutions for addressing the new demands of educational aspirants generating from continuous changes. Being the Editor-in-Chief of the New Perspective Journal of Business and Economics, it is great honour to showcase the unique practices of KCM and encourage other institutions to adopt similar approaches in their teaching methodologies. The editorial acknowledges the intellectual support from researchers, scientists and academicians along with college administration and all supporting hands without their support it could not be brought. Authors are young mind and their efforts are real expression of their dedication under guidance of experienced research professors and peer reviewers. Kindly keep giving your feedback to us for further improvements.